Isobaric vapor-liquid equilibrium for binary system of methyl caprylate + methyl caprate at 2, 6 and 10 kPa. (March 2017) - Ke, Wenjing; Ding, Hui; Gao, Yujie; Liu, Shejiang; Xing, Zhongpeng; Gui, Jianzhou; Liu, Dan
Highlights: The VLE data for binary system methyl caprylate and methyl caprate were measured. The Wilson, NRTL and UNIFAC models were used to reproduce the experimental values. The COSMO-SAC model was applied to predict the VLE of the binary system. All four models provided great reproductions, especially the NRTL model. Abstract: The isobaric vapor-liquid equilibrium data for the binary system methyl caprylate (1) + methyl caprate (2) at 2, 6 and 10 kPa were measured with a modified Othmer still. All the experimental data were verified to be thermodynamically consistent according to the Van Ness test method. Two activity coefficient models (Wilson and NRTL) were applied to regress the experimental values. Furthermore, the group contribution method (UNIFAC) and the COSMO-SAC model were also employed to predict vapor-liquid equilibrium data. The four models reproduced the experimental values very well, while the NRTL model provided a slightly better result than the other three models, with the root mean square deviations of temperature and vapor-phase mole fraction less than 0.36 K and 0.0042, respectively.